2006
DOI: 10.1016/j.ydbio.2006.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The function of a Drosophila glypican does not depend entirely on heparan sulfate modification

Abstract: Division abnormally delayed (Dally) is one of two glycosylphosphatidylinositol (GPI)-linked heparan sulfate proteoglycans in Drosophila. Numerous studies have shown that it influences Decapentaplegic (Dpp) and Wingless signaling. It has been generally assumed that Dally affects signaling by directly interacting with these growth factors, primarily through its heparan sulfate (HS) chains. To understand the functional contributions of HS chains and protein core we have (1) assessed the growth factor binding prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 46 publications
4
91
1
Order By: Relevance
“…As one of our mechanistic questions, we examined whether HS modification is critical for trans signaling. Recent studies have shown that in some in vivo contexts, the activities of glypicans reside in the core protein moiety (24,25). In contrast, our analyses showed that the trans co-receptor activity of DALLY requires its HS modification.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…As one of our mechanistic questions, we examined whether HS modification is critical for trans signaling. Recent studies have shown that in some in vivo contexts, the activities of glypicans reside in the core protein moiety (24,25). In contrast, our analyses showed that the trans co-receptor activity of DALLY requires its HS modification.…”
Section: Discussioncontrasting
confidence: 59%
“…Recent studies showed that glypicans retain an unexpected level of activity without modification by glycosaminoglycan sugar chain (24,25).…”
Section: Dally Enhances Dpp Signaling In Drosophila S2mentioning
confidence: 99%
“…In developing Drosophila pupal wings, zebrafish embryos and Xenopus embryos, one of the proposed roles for the BMP-binding protein Crossveinless-2 (Cv-2) is that it regulates the accessibility of ligand to type I receptors (a schematic of the proposed mechanism in Drosophila is shown in figure 1b). The mechanism in figure 1b is a characterization of the proposed action for numerous other regulators, including heparan sulphate proteoglycans (HSPGs) such as Dally [14] and Dally-like [15,16], collagen [17] and others such as BAMBI (bone morphogenetic protein and activin membrane-bound inhibitor) [18]. We refer to the molecules that regulate receptorligand interaction akin to the schematic in figure 1b as surface-associated BMP-binding proteins (SBPs).…”
Section: Introductionmentioning
confidence: 99%
“…Such data suggest that HSPG core proteins can function largely as inert and interchangeable scaffolds. However, other evidence suggests that both core proteins and GAG chains may contribute to Hh signaling (see below) and to canonical and noncanonical Wnt signaling (10)(11)(12)(13)(14)(15). For example, loss of GAG modification clearly disrupts Hh ligand movement in Drosophila (9), although a specific requirement for GAG chains or core protein in cell-autonomous response in vivo has not been established.…”
mentioning
confidence: 99%